Sucre à la crème: Origin and Trajectory of an Authentic Québec Confection - Charbonneau, Patrick (Ethnologies, 2024)
Although the emergence of sucre à la crème left little paper trail, various lines of evidence point toward a late 18th -early 19th century origin in rural French-speaking communities of the St. Lawrence River Valley. Successful preparation of the confection relied on a mastery of sugar crystallization, which was common among contemporary maple sugar makers, but few others. Such humble beginnings have colored perceptions of the sweet ever since. Early Canadian cookbooks, which mostly adapted European cuisine to a local context, neglected it. Sucre à la crème nevertheless spread widely. The ubiquity and distinctness of the dish have loaded it with cultural meaning. And yet, many food historians and ethnographers have sought an exogeneous origin for it, thus perpetuating received ideas about the history of Québec eating and drinking. Using a variety of historical and ethnographic sources as well as insight from physical chemistry, this article attempts to redress the history of sucre à la crème.